1995
DOI: 10.1007/bf00169382
|View full text |Cite
|
Sign up to set email alerts
|

Nonexocytotic noradrenaline release and ventricular fibrillation in ischemic rat hearts

Abstract: In myocardial ischemia, nonexocytotic noradrenaline release has been identified as underlying mechanism of ischemia-evoked noradrenaline release. Nonexocytotic noradrenaline release can be suppressed by inhibitors of the neuronal noradrenaline carrier (uptake), such as desipramine. Utilizing this pharmacological intervention the role of local noradrenaline release in the genesis of ischemia-induced ventricular arrhythmias was studied. Regional ischemia was induced in rat isolated perfused hearts by ligature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 13 publications
(12 reference statements)
0
29
0
Order By: Relevance
“…20,23,24 Most recently, we found that the attenuation of NE overflow after ischemia/reperfusion resulted in a marked improvement in postischemic cardiac dysfunction in isolated rat hearts. 33 Several investigations have also indicated that there is a direct correlation between NE release and the severity of reperfusion arrhythmia in postischemic guinea pig, 23 rat, 43 and mouse 44 hearts. Furthermore, it has been demonstrated that increased plasma NE levels in patients with asymptomatic left ventricular dysfunction appear to predict all-cause and cardiovascular mortality and the development of clinical events related to the onset of heart failure or acute ischemic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,24 Most recently, we found that the attenuation of NE overflow after ischemia/reperfusion resulted in a marked improvement in postischemic cardiac dysfunction in isolated rat hearts. 33 Several investigations have also indicated that there is a direct correlation between NE release and the severity of reperfusion arrhythmia in postischemic guinea pig, 23 rat, 43 and mouse 44 hearts. Furthermore, it has been demonstrated that increased plasma NE levels in patients with asymptomatic left ventricular dysfunction appear to predict all-cause and cardiovascular mortality and the development of clinical events related to the onset of heart failure or acute ischemic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Postischemic reperfusion is associated with high levels of NE release into the coronary perfusate caused by reversal of the NE transporter (NET) under ischemic conditions (carrier-mediated NE release) (9,20). The experimental protocol utilized in the present study (30-min global ischemia) has been shown to result in carrier-mediated NE release (6).…”
Section: [ 3 H]ne Uptake In Cardiac Synaptosomesmentioning
confidence: 99%
“…In recent years, the finding has been established that myocardial ischemia leads to local-metabolic, nonexocytotic noradrenaline release, which contributes to the generation of arrhythmias (Schömig et al 1984(Schömig et al , 1986Dietz et al 1989;Kurz et al 1995). This concept implies that noradrenaline displays an arrhythmogenic action by stimulating adrenergic receptors, and thus it can be concluded that adrenoceptor antagonists protect against arrhythmias evoked by ischemia.…”
Section: Introductionmentioning
confidence: 99%